A highly diastereoselective recognition process as the basis for the resolution of palladatricyclo[4.1.0.0 2,4]heptanes - Hashmi, A. Stephen K.; Riedel, Dominic; Rudolph, Matthias (Organometallics, 2012)
The synthesis of palladatricyclo[4.1.0.02,4]heptane diastereomers by positional selective transesterification with (1R,2S,5R)(−)-menthol is used for the resolution of these chiral organometallic compounds. The separation process of the two diastereomers is simplified by an unprecedented aggregation phenomenon. In a molecular recognition process the highly diastereoselective formation of dimers of strongly differing stability allows an efficient separation by normal column chromatography. The stereoselective dimerization was proven by IR and mass spectroscopic studies as well as 1H NMR techniques and X-ray crystal structure analysis.